2001
DOI: 10.1351/pac200173081281
|View full text |Cite
|
Sign up to set email alerts
|

Developments in CO2 research

Abstract: CO 2 can be a good solvent for many compounds when used in its compressed liquid or supercritical fluid state. Above its critical temperature and critical pressure (T c = 31 °C, P c = 73.8 bar), CO 2 has liquid-like densities and gas-like viscosities, which allows for safe commercial and laboratory operating conditions. Many small molecules are readily soluble in CO 2 , whereas most macromolecules are not. This has prompted development of several classes of small molecule and polymeric surfactants that enable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…The mild temperature conditions (50 °C, 220 bar) are of special interest for these precursor compounds because the latter can be carboxylated before thermal degradation of the Cp ligands occurs. [35][36][37] whose crystal structure was refined based on XRPD data by the Rietveld method. [16] The overall yield of Ln 2 O 2 CN 2 obtained in four reaction steps based on Cp 3 Ln as starting material (Scheme 1) is > 25 mol %.…”
Section: Reactive Lanthanide Nitride Materialsmentioning
confidence: 99%
“…The mild temperature conditions (50 °C, 220 bar) are of special interest for these precursor compounds because the latter can be carboxylated before thermal degradation of the Cp ligands occurs. [35][36][37] whose crystal structure was refined based on XRPD data by the Rietveld method. [16] The overall yield of Ln 2 O 2 CN 2 obtained in four reaction steps based on Cp 3 Ln as starting material (Scheme 1) is > 25 mol %.…”
Section: Reactive Lanthanide Nitride Materialsmentioning
confidence: 99%
“…[ 29,32] Additionally, the deformation vibrations of N-H and O-C-N can be located at 1272, 1112, 859, and 695 cm -1 . [29,32] Heterogeneous Solid-Gas Reactivity of [Ce{N(SiMe 3 ) 2 } 3 ] Towards CO 2 The structure of Ce-BTMSA has been determined elsewhere [18] and revealed a mononuclear species with the Ce III ion in the center of the three BTMSA ligands (CN = 3). It has been shown that the central atom displays a disorder in the z direction, occupying two sites positioned above and below the plane formed by the ligand nitrogen atoms.…”
Section: Characterization Of Ammonium Carbamatementioning
confidence: 99%
“…[1][2][3][4][5][6] Novel methods to sufficiently activate CO 2 for an application in organic and inorganic solvent reactions have been reported emphasizing the potential of this compound in various processes. [7][8][9][10][11][12] We have discovered a novel approach for this "green" reagent as a pre-organized C/O donor in solid-state reactions for the synthesis of novel mixed N-containing lanthanide derivatives of carbonato compounds, which can be described as oxonitridocarbonates (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Moreover it is a well-established fact that CO 2 in its supercritical state can be a good solvent for many low molecular weight molecules. 7,8 Furthermore, CO 2 is inexpensive, nonflammable and environmentally benign. These properties of CO 2 in its supercritical state have motivated us to examine the feasibility of extracting porogens using SCCO2 treatment to form nanopores.…”
mentioning
confidence: 99%